Pengembangan Media Kartu Kata Bergambar untuk Meningkatkan Kemampuan Membaca Permulaan Anak Kelompok B di RA Roszaini Husna - Zulvia Zulvia; Fahruddin Fahruddin; Ika Rachmayani; I Made Suwasa Astawa (Indonesian Publication Center, 2021)
Picture word card media is a card that presents pictures that are equipped with words, each picture has its own meaning, description and interpretation, can facilitate and strengthen children's memories, add insight and skills. Beginning reading is reading that is taught programmatically to preschoolers. The purpose of this study was to determine the use of picture word card media to improve the reading ability of children in group B at RA Roszaini Husna. This research is a development research which is a type of descriptive qualitative research. The subjects used in this study were 6 group B children. The data analysis technique used in this research is descriptive qualitative analysis technique. The results showed that using picture word cards media could improve the early reading ability of group B children. This can be seen from the final results of the assessment of group B children who in the pre-test assessment got a score of 44.38% and post-test of 92.29% so that the final score obtained by group B is 47.92% which is included in the high category.